IDENTIFIKASI JENIS KAYU PERDAGANGAN DAN KURANG DIKENAL YANG DIPERDAGANGKAN DI SURABAYA - Nenny Sumarliani (Jurnal Penelitian Hasil Hutan, 1992)
Survey  of  commercial  and  lesser known   wood  species  marketed   in Surabaya  has been conducted.   The survey  result  from  several  companies  shows  that  there  are 21  commercial  wood  species represented   by 10 families and 10 trade names.  The  trade name used in Surabaya  is similar to those  listed  in the official  Indonesian   Timber  nomen  clature. A  tentative  identification   key  of  the  above  wood  species  is presented   in this  paper.